2021
DOI: 10.1097/hjh.0000000000002987
|View full text |Cite
|
Sign up to set email alerts
|

Association of proteinuria and hypertension with incident atrial fibrillation in an elderly population: nationwide data from a community-based elderly cohort

Abstract: Objective: The excess risk of atrial fibrillation in relation to the presence of proteinuria associated with hypertension has not been well elucidated. We aimed to determine the effect of hypertension and/or proteinuria on the incidence of atrial fibrillation. Second, we evaluated whether the associations with temporal changes in proteinuria status on the incidence of atrial fibrillation. Methods and results: A total of 85 434 participants with hypertension and 125 912 part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Studies have reported that ameliorating proteinuria reduced the risk of cardiovascular events, 35,36 whereas conflicting results also existed. 34,37 Due to the observational nature of our study, it was therefore difficult to explain the exact mechanism between proteinuria and the risk for incident AF. Proteinuria is widely accepted as a marker reflecting systemic endothelial dysfunction, inflammatory cytokine activation, impaired oxidative metabolism, and insulin resistance.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Studies have reported that ameliorating proteinuria reduced the risk of cardiovascular events, 35,36 whereas conflicting results also existed. 34,37 Due to the observational nature of our study, it was therefore difficult to explain the exact mechanism between proteinuria and the risk for incident AF. Proteinuria is widely accepted as a marker reflecting systemic endothelial dysfunction, inflammatory cytokine activation, impaired oxidative metabolism, and insulin resistance.…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, a prior meta-analysis has showed that elevated ACR was significantly associated with a greater risk of incident AF. 11 Park et al 34 showed that participants with persistent proteinuria had higher cumulative incidence of AF compared with the participants who had consistently negative results. These findings highlight that a long-term exposure to proteinuria may significantly increase the risk of AF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 In addition, proteinuria is a signi cant determinant in the development of incident AF. 13,14 Meanwhile, proteinuria can develop…”
Section: Introductionmentioning
confidence: 99%
“…About 60-80% of AF patients have HBP (2), and persistently elevated blood pressure (BP) is one of the important risk factors for AF (3)(4)(5). Conversely, patients with HBP are about several times more likely to develop AF than those with normal BP (6,7). Studies have also shown that high normal BP increases the risk of AF in middle-aged individuals (6,8).…”
Section: Introductionmentioning
confidence: 99%